2021
DOI: 10.3389/fchem.2021.689735
|View full text |Cite
|
Sign up to set email alerts
|

A Methylene Blue Assisted Electrochemical Sensor for Determination of Drug Resistance of Escherichia coli

Abstract: Due to the abuse of antibiotics in clinical, animal husbandry, and aquaculture, drug-resistant pathogens are produced, which poses a great threat to human and the public health. At present, a rapid and effective drug sensitivity test method is urgently needed to effectively control the spread of drug-resistant bacteria. Using methylene blue as a redox probe, the electrochemical signals of methylene blue in drug-resistant Escherichia coli strains were analyzed by a CV method. Graphene ink has been used for enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Rongshuai Duan et. al 33 presents a study showcasing the detection of resistant Escherichia coli bacteria by employing Methylene Blue as an electron acceptor to observe bacterial respiration. Additionally, they utilized graphene ink to augment the electrochemical response for enhanced detection.…”
Section: Electrochemical Phenotypic Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Rongshuai Duan et. al 33 presents a study showcasing the detection of resistant Escherichia coli bacteria by employing Methylene Blue as an electron acceptor to observe bacterial respiration. Additionally, they utilized graphene ink to augment the electrochemical response for enhanced detection.…”
Section: Electrochemical Phenotypic Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Approaches akin to microbial fuel cell systems have also been reported where measurement of the total accumulated energy and its correlation with gold standard MIC assays was demonstrated using the common pathogen Pseudomonas aeruginosa [24]. Methylene blue has been used as a redox probe to measure microbial metabolism and in the process showing that sensitivity of four E. coli isolates to ciprofloxacin, gentamicin, and ampicillin could be readily established [25]. In addition to these methods highlighted, several other studies have reported viable routes to determining AST in a phenotypic manner [26]- [33].…”
Section: Phenotypic Approachesmentioning
confidence: 99%
“…In recent years, food poisoning caused by foodborne pathogens has frequently occurred worldwide, which is the most prominent public health problem in the world (Hou et al, 2020;Duan et al, 2021). As one of the most hazardous foodborne pathogens, Escherichia coli (E. coli) O157:H7 can cause some diseases such as hemorrhagic colitis and hemolytic uremic syndrome.…”
Section: Introductionmentioning
confidence: 99%